Redundancy of mammalian Y family DNA polymerases in cellular responses to genomic DNA lesions induced by ultraviolet light. Issue 17 (28th August 2014) - Jansen, Jacob G.; Temviriyanukul, Piya; Wit, Niek; Delbos, Frédéric; Reynaud, Claude-Agnès; Jacobs, Heinz; de Wind, Niels
Abstract: Short-wave ultraviolet light induces both mildly helix-distorting cyclobutane pyrimidine dimers (CPDs) and severely distorting (6–4) pyrimidine pyrimidone photoproducts ((6–4)PPs). The only DNA polymerase (Pol) that is known to replicate efficiently across CPDs is Polη, a member of the Y family of translesion synthesis (TLS) DNA polymerases. Phenotypes of Polη deficiency are transient, suggesting redundancy with other DNA damage tolerance pathways. Here we performed a comprehensive analysis of the temporal requirements of Y-family Pols ι and κ as backups for Polη in (i) bypassing genomic CPD and (6–4)PP lesions in vivo, (ii) suppressing DNA damage signaling, (iii) maintaining cell cycle progression and (iv) promoting cell survival, by using mouse embryonic fibroblast lines with single and combined disruptions in these Pols. The contribution of Polι is restricted to TLS at a subset of the photolesions. Polκ plays a dominant role in rescuing stalled replication forks in Polη-deficient mouse embryonic fibroblasts, both at CPDs and (6–4)PPs. This dampens DNA damage signaling and cell cycle arrest, and results in increased survival. The role of relatively error-prone Pols ι and κ as backups for Polη contributes to the understanding of the mutator phenotype of xeroderma pigmentosum variant, a syndrome caused by Polη defects.